Efficacy of electroacupuncture for insomnia in cancer patients: a systematic review and meta-analysis - Liu, Xiaodong; Xu, Ning; Wang, Shangpei; Jia, Qingjun (Frontiers in Neurology, 2025)
BackgroundInsomnia is a prevalent symptom among cancer patients. Electroacupuncture (EA) has been widely applied in managing sleep disorders, particularly in cancer patients or those experiencing insomnia.ObjectivesThis meta-analysis aims to evaluate the efficacy and safety of electroacupuncture for treating cancer-related insomnia.MethodsTwo independent reviewers conducted comprehensive searches across multiple databases, including EMBASE, Web of Science, PubMed, the Cochrane Library, Wanfang Digital Journals, China National Knowledge Infrastructure (CNKI), and the VIP Database for Chinese Technical Periodicals. The search was completed on April 28, 2024. The reviewers independently performed literature screening, data extraction, and risk of bias (ROB) assessment using the revised Cochrane ROB tool. Data were analyzed using RevMan 5.4 and Stata 15.0 software.ResultsEight randomized controlled trials (RCTs) involving 550 patients (305 in the experimental group and 245 in the control group) were included. EA significantly reduced Pittsburgh Sleep Quality Index (PSQI) scores (SMD = −0.86, 95% CI [−1.24, −0.49], p < 0.001), Insomnia Severity Index (ISI) scores (SMD = −1.14, 95% CI [−1.59, −0.69], p < 0.001), sleep latency (SL) (SMD = −0.48, 95% CI [−0.73, −0.23], p < 0.001), and sleep disturbance (SDB) (SMD = −0.44, 95% CI [−0.73, −0.16], p = 0.002). EA also significantly lowered Hospital Anxiety and Depression Scale-Anxiety (HADS-Anxiety) scores (SMD = −0.59, 95% CI [−0.91, −0.26], p < 0.001) and Hospital Anxiety and Depression Scale-Depression (HADS-Depression) scores (SMD = −0.73, 95% CI [−1.06, −0.40], p < 0.001), while increasing total sleep time (TST) (SMD = 0.65, 95% CI [0.14, 1.17], p = 0.013). No significant differences were observed in the Athens Insomnia Scale (AIS), sleep duration (SD), sleep efficiency (SE), or sleep quality (SQ) scores between the EA and control groups.ConclusionElectroacupuncture has shown promising potential in treating cancer-related insomnia by increasing total sleep time and reducing sleep disturbances. However, additional high-quality studies are necessary to validate these findings.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=567567, Identifier CRD42024567567.